Efek Penambahan Etanol Pada Bahan Bakar Pertamax Terhadap Performa Motor Satria F 150 - D. Suanggana; K.D. Radyantho; D.A. Puspitasari (Dinamika Teknik Mesin, 2023)
A type of renewable energy is ethanol. One of ethanol’s advantages is its very high octane value so that the combustion process in the combustion chamber can burn perfectly and reduce knocking. This study aims to analyze the effect of adding ethanol to Pertamax fuel on the performance of the satria F 150 motorcycle. The research method used is the experimental method, where the fuel tested is EX0 (Ethanol 0%: Pertamax 100%), EX5 (Ethanol 5%: Pertamax 95%), EX10 (Ethanol 10%: Pertamax 90%), EX15 (Ethanol 15%: Pertamax 85%) and EX20 (Ethanol 20%: Pertamax 80%). Based on the research results, the torque and power produced by EX0 fuel are 13.78 Nm and 10.73 kW, EX5 fuel is 13.63 Nm and 11.45 kW, EX10 is 15.18 Nm and 11.79 kW, EX15 is 15.45 Nm and 12.01 kW, and the EX20 is 15.20 Nm and 11.94 kW. The results for EX0, EX5, EX10, EX15, and E20 with the lowest specific fuel consumption were 0.110 kg/kWh for EX0, 0.104 kg/kWh for EX5, 0.081 kg/kWh for EX10, 0.073 kg/kWh for EX15, 0.099 kg/kWh for EX20. For the best performance, EX15 fuel is the best combination.